Holobiont suture zones: Parasite evidence across the European house mouse hybrid zone. Issue 24 (10th December 2018) - Goüy de Bellocq, Joëlle; Wasimuddin,; Ribas, Alexis; Bryja, Josef; Piálek, Jaroslav; Baird, Stuart J. E.
Abstract: Parasite hybrid zones resulting from host secondary contact have never been described in nature although parasite hybridization is well known and secondary contact should affect them similarly to free‐living organisms. When host populations are isolated, diverge and recontact, intimate parasites (host specific, direct life cycle) carried during isolation will also meet and so may form parasite hybrid zones. If so, we hypothesize these should be narrower than the host's hybrid zone as shorter parasite generation time allows potentially higher divergence. We investigate multilocus genetics of two parasites across the European house mouse hybrid zone. We find each host taxon harbours its own parasite taxa. These also hybridize: Parasite hybrid zones are significantly narrower than the host's. Here, we show a host hybrid zone is a suture zone for a subset of its parasite community and highlight the potential of such systems as windows on the evolutionary processes of host–parasite interactions and recombinant pathogen emergence.